Simulação numérica e experimentos de estampagem com diferentes modelos tribológicos - Stürme, Lindofo (2021)
This work presents a study on the tribological conditions in the sheets forming process and its relations with the stamped product, through numerical simulation and experimental tests; and a case study using generated tribological models, considering the roughness of the tool in two levels, with three lubrication levels, correlating them with the type of sheet material. At the same time, it was performed a simulation with the conventional Coulomb’s friction model for the comparison of results. It has validated the simulations throughout experimental tests by using a tests tool in a factory facility. It has subjected the shaped parts to measurements of the bends and thicknesses, and it has been analyzed the measurements statistically. The results of the simulations using the calculated tribological models showed which, among all the tested variations, the part’s thickness has the smallest dimensional change with the combination of roughness between Sa= 0.4 μm and 3 g/m2 of lubricant, this combination has also been responsible for the best flow of material over the tool, resulting in smaller bends. Meanwhile, the simulation using the conventional Coulomb’s model resulted in smaller thicknesses and larger bends, in other words, greater restriction to the flow of the sheet over the tool. As for practical experiments, in terms of thickness reduction, the statistical analysis has evidenced that the quantities of tested lubricants did not exert a significant influence. Thus, considering the cost-benefit, the ideal tribological condition for thickness conservation was the tool with roughness Sa= 0.4 μm, in conjunction with the addition of 0.5 g/m2 of lubricant. In terms of bend dimensions, the statistical analysis showed that both the roughness variable of the tool and the quantity variable of the lubricant exerted a significant influence on the dimensional results. The amount of 3 g/m2 of lubricant resulted in much smaller bends compared to other lubrication conditions, mainly on 0.4 μm roughness, which is the recommended combination. As for the comparisons between simulation and practical experiments, in terms of thickness reduction was found that the stamped components resulted in thickness around 4% lower compared to the simulations with the calculated tribological models around 3% lower compared to the conventional Coulomb’s friction model. The measurements of the bends, in turn, had an average variation of around 2% in comparison with the simulations. For the study conditions of this work, and based on the obtained results, the option to use the conventional Coulomb’s friction model for numerical simulations is justified.